Analysis of Resilience and Competence on Employee Performance through Intervening Key Performance Indicator Variables - Primadi Candra Susanto; Wastam Wahyu Hidayat; Tri Widyastuti; Zahara Tussoleha Rony; Josua Panatap Soehaditama (Indonesian Journal of Business Analytics, 2023)
In this scientific article, the purpose of the study is to provide an overview of the variables that exist in the research article with existing results, also provide evidence of these results and provide reinforcement by researchers. It is expected that scientific articles provide a gap, which can provide a contribution to scientific results, the research method used is qualitative from the results of analysis of scientific articles originating from journals of national and international reputation with research results that are corroborated by researchers. The results of the research of the variables in this study than the variables found have a positive influence, proven by the exposure of scientific results, and this scientific article provides reinforcement of the results of existing research with research variables that have been previously studied. In this scientific article, it was found that there are several other variables that can be used in further research for the future or the next.